Biohydrogen Production by Reusing Immobilized Mixed Culture in Batch System - Astrilia Damayanti; Sarto Sarto; Wahyudi Budi Sediawan (International Journal of Renewable Energy Development, 2020)
Biohydrogen production via dark fermentation is a prospective renewable energy technology. In the process, reused of immobilized mixed culture is very important as their activities greatly influencehydrogen production. The aim of this work was to evaluate the reuse of alginate beads affecting the biohydrogen production for 45 days. This study in batch reactor were performed using glucose 10 M as substrate, alginate and activated carbon as immobilization matrix materials, chicken eggshell as buffer, and cow dung biodigester as mixed culture. Hydrogen and pH on fermentation product are investigated by gas chromatography (GC) technique and pH meter, respectively. The colony diameter on immobilized and co-immobilized mixed culture was observed using optical microscope and colony diameter was measured using Image-Pro Plus Software v4.5.0.29. The surface morphology of immobilization and co-immobilization beads were determined using scanning electron microscope (SEM). The results showed that the colonies growth observed using optical microscopy or SEM was apparent only in the immobilization of mixed culture. The average growth and diameter of colonies per day were 90 colonies and 0.025 mm, respectively. The weight of beads and pH during the 45-day fermentation process for bead immobilization of mixed culture were 1.32–1.95 g and 6.25–6.62, correspondingly, meanwhile, the co-immobilizations of the mixed culture were 1.735–2.21g and 6.25–6.61, respectively. In addition, the average hydrogen volume of glucose fermented using an eggshell buffer and reusing the immobilization and co-immobilization beads was 18.91 mL for 15 cycles.©2020. CBIORE-IJRED. All rights reserved